Beyond Metal Silos: Low-cost Hermetic Bags for Smallholder Grain Protection - Oyewole, O. S.; Raji, M. A. (International Journal of Bio-resource and Stress Management, 2026)
This review was conducted in August, 2025 at Nigerian Stored Products Research Institutes, Ibadan, Nigeria to examine post-harvest losses and hermetic storage technologies for smallholder farmers in Sub-Saharan Africa. Post-harvest management plays a crucial role in preserving the quantity and quality of staple grains in developing countries, where over 500 million smallholder farmers produce the majority of food. This research article reviewed the transition from metal silos to low-cost hermetic bags as a sustainable and effective solution for post-harvest grain storage among smallholder farmers in developing countries. While metal silos offer effective protection, their high cost, technical complexity, and spatial demands limit adoption by smallholders. Hermetic bags, including prominent brands like Purdue Improved Crop Storage (PICS™), GrainPro, ZeroFly®, AgroZ®, Elite and Storezo, present cost-effective, flexible, and scalable alternatives. These bags create airtight conditions that induce hypoxia, stopping insect pests’ development and grain spoilage without chemical use. Comparative studies show hermetic bags can reduce losses by up to 100% for major pests such as Callosobruchus maculatus and Prostephanus truncatus, with economic benefits ranging from 32–69% cost savings and favorable benefit-cost ratios (above 1.6), making them accessible to resource-limited farmers. Field trials across Sub-Saharan Africa and Asia confirm their efficacy in maintaining grain quality, reducing insect infestation, and lowering weight loss compared to traditional storage methods. However, challenges remain regarding the environmental impacts of plastic waste, variation in gas barrier properties among products, and liner durability. The article concluded that hermetic bags had evolved from alternatives to metal silos to essential components of smallholder post-harvest management. Future efforts must focus on developing biodegradable materials, standardizing performance metrics, improving reusability, and addressing recycling infrastructure to ensure sustainable adoption.